Demographic and clinical characteristics of lithium‐treated older adults with bipolar disorder. (26th July 2022) - Forlenza, Orestes V.; Hajek, Tomas; Almeida, Osvaldo P.; Beunders, Alexandra J. M.; Blumberg, Hilary P.; Briggs, Farren B. S.; De‐Paula, Vanessa J. R.; Dols, Annemiek; Eyler, Lisa T.; Forester, Brent P.; Gildengers, Ariel; Jimenez, Esther; et al.
Abstract: Objectives: There is limited information on the characteristics of older adults with bipolar disorder (OABD) treated with lithium, along with safety concerns about its use by older adults. The aim of the present study is to describe the demographic and clinical characteristics of OABD receiving lithium therapy, using data from the Global Ageing & Geriatric Experiments in Bipolar Disorder (GAGE‐BD). Experimental Procedures: Cross‐sectional analysis of the GAGE‐BD dataset to determine differences and similarities between lithium users and non‐users. We analysed data from 986 participants aged 50 years or older (mean age 63.5 years; 57.5% females) from 12 study sites. Two subgroups ('Lithium'; 'Non‐lithium') were defined according to the current prescription of lithium. We compared several outcomes between these groups, controlling for age, gender, and study site. Results: OABD treated with lithium had lower scores on depression rating scales and were less likely to be categorised as with moderate or severe depression. There was a lower proportion of lithium users than non‐users among those with evidence of rapid cycling and non‐bipolar psychiatric diagnoses. Assessment of global cognitive state and functionality indicated better performance among lithium users. The current use of antipsychotics was less frequent among lithium users, who also reported fewer cardiovascular comorbidities than non‐users. Conclusion: We found several potentially relevant differences in the clinical profile of OABD treated with lithium compared with those treated with other mood stabilisers. However, the interpretation of the present results must take into account the methodological limitations inherent to the cross‐sectional approach and data harmonisation.